The Tipped Balance of ILC1/ILC2 in Peripheral Blood of Oral Lichen Planus Is Related to Inflammatory Cytokines - Wang, Zi-Ming; Zhang, Jing; Wang, Fang; Zhou, Gang (Frontiers in Cell and Developmental Biology, 2022)
Oral lichen planus (OLP) is an immune-inflammatory disease mediated by T cells. Innate lymphoid cells (ILCs) constitute a novel family of immune cells that initially originate from common innate lymphoid progenitors. Termed “T cells counterparts,” ILCs play a prominent role in inflammatory-immune diseases. However, the characterization of ILCs and their related induced factors were unclear in OLP. In the present study, the phenotypic characteristics of ILCs and their correlation with inflammatory cytokines were explored in the peripheral blood of OLP patients and healthy controls. We found that the proportion of total ILCs was expanded in OLP and was positively correlated with disease severity. The highly skewed distribution of ILC subpopulations was notable in OLP. Specifically, the frequency of ILC1s was significantly increased, while that of ILC2s was significantly reduced in total ILCs of OLP, resulting in the markedly elevated ILC1/ILC2 ratio in OLP. Correspondingly, ILCs in OLP displayed high expression of T-bet but low expression of GATA3. In addition, the IFN-γ expression level was elevated in ILC1s, whereas the IL-4 expression level was decreased in ILC2s. Moreover, ILC-associated activators IL-12, IL-18, and IL-1β were upregulated in OLP plasma, with IL-12 and IL-1β both positively correlated with the ILC1/ILC2 ratio. Further in vitro stimulation tests indicated that OLP plasma remarkedly increased the ILC1/ILC2 ratio, especially that IL-12 and IL-1β tipped the balance between ILC1s and ILC2s toward ILC1s in total ILCs. Overall, elevated levels of IL-12 and IL-1β might act as environmental cues in tipping the balance of ILC1/ILC2 in the peripheral blood of OLP, contributing to the immune dysregulation in OLP.